Artyfyshall Bird. A collection of pre-digital generative models for music composition from the period between 1600 and 1850. - Cornia, Nicholas 1989- (GitHub, 2024)
A collection of pre-digital generative models for music composition from the period between 1600 and 1850. Part of the music tratises has been transcribed in Lilypond format and emulated with a Python implementation using the Abjad library.The code is part of publication of the authors for ISMIR 2024.
https://github.com/NicholasCorniaOrpheus/Artyfyshall-Bird/blob/main/README.md
FRIS
Keywords: Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Algorithmic composition